Developing a guideline for transferring premature infants from an incubator to an open crib. Issue 3 (June 2020) - Jacob, Ani; Casatelli, Joanne
Abstract: The purpose was to identify guidelines for successful transfer of stable preterm infants from an incubator to open crib while maintaining thermoregulation within the acceptable axillary temperature of 36.5–37.20 C. The results shows that weight is not the primary criteria for a successful transfer, rather the brain maturity of the infants. The incubator weaning should be gradual and when the incubator temperature is weaned to 26.80–26.9 °C with infant's temperature within acceptable range for 24 h (with a t-shirt, hat and wrapped in one blanket), the infant may be weaned successfully to an open crib. The study concludes that most preterm infants are mature enough to maintain neutral thermoregulation outside of an incubator by 34.4–35 weeks post menstrual age regardless of their weight.